2015
DOI: 10.1002/2015pa002782
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition and speciation of sedimentary nitrogen and carbon in the Okinawa Trough over the past 30 ka

Abstract: Total organic carbon to total nitrogen ratios (C/N) and their isotopic compositions (δ 13 C TOC and δ 15 N TN ) are oft-applied proxies to discern terrigenous from marine-sourced organics and to unravel ancient environmental information. In high depositional Asian marginal seas, the inclusion of N-bearing minerals in the bulk sediment dilutes or masks signals sought after in δ 15 N and δ 13 C analyses, thus leading to incorrect and even contradictory interpretations. We used KOH-KOBr to separate operationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…We found that 25.7 ± 4.2%, 44.4 ± 5.0%, and 31.9 ± 7.6% of the total N occurred as inorganic N (N fix ) fraction in the surface soils of mangroves, saltmarshes, and seagrasses, respectively. Additionally, the percentages of KOBr-resistant OC (OC res ), likely dominated by black carbon and some lithogenic kerogen, were consistent with the significant contribution of black carbon (9–25%) with ages of 4097–15907 BP in deltaic BCEs . The δ 13 C res values of mangroves and seagrasses were higher and lower, respectively, than the δ 13 C tot and δ 13 C KOBr values (Figure b, Table S4).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…We found that 25.7 ± 4.2%, 44.4 ± 5.0%, and 31.9 ± 7.6% of the total N occurred as inorganic N (N fix ) fraction in the surface soils of mangroves, saltmarshes, and seagrasses, respectively. Additionally, the percentages of KOBr-resistant OC (OC res ), likely dominated by black carbon and some lithogenic kerogen, were consistent with the significant contribution of black carbon (9–25%) with ages of 4097–15907 BP in deltaic BCEs . The δ 13 C res values of mangroves and seagrasses were higher and lower, respectively, than the δ 13 C tot and δ 13 C KOBr values (Figure b, Table S4).…”
Section: Resultssupporting
confidence: 63%
“…Although allochthonous particle deposition and mineral protection are key biogeochemical controls of OC accumulation in BCEs, we observed distinct mineral effects on N and P fractions and OC density (Figure ), suggesting different roles for minerals during transportation and deposition of these three elements. During transportation, large riverine allochthonous inputs promote the accumulation of recalcitrant N and P fractions because clay minerals (e.g., Illite) are the dominant carrier of inorganic N (N fix ) and many negatively charged P species are strongly adsorbed to positively charged mineral surfaces (e.g., amorphous Al/Fe oxides); , thus, they may dilute the relatively labile organic fractions, which together with autochthonous OC have proven to be important fractions contributing to OC preservation according to our model results. After deposition, the physical protection provided by minerals and aggregates, if it exists, and the formation of organomineral complexes , may facilitate accumulation of autochthonous OC mainly originating from plant–microbe interactive residuals or dissolved OC. , These results provide empirical evidence that terrestrial (riverine)-dominated BCEs are beneficial for preservation of refractory and mineral-bound organic matter and nutrients and increase the adaptive capacity of BCEs to cope with climate change.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Moreover, clay mineral evidence illustrates that the relative contributions of lithogenic particles from the adjacent land present a distinct variability from the last glaciation to the Holocene [e.g., Liu et al ., ]. Since the clay‐fixed N may carry the climate information from land and the occupation of clay‐fixed N in total N is relatively high in China's marginal seas [ Zheng et al ., ], it is conceivable that changes in climate and the sediment source region may have also led to the variability of down‐core δ 15 N sed .…”
Section: Discussionmentioning
confidence: 99%